FORMATION OF DIGITAL LITERACY FOR TEACHERS IN THE SYSTEM OF POSTGRADUATE EDUCATION IN UKRAINE - Olesia Stoika (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article discusses the problem of forming digital literacy for teachers in the system of postgraduate education in Ukraine. It is noted that digital literacy is important for teachers as it can contribute to enhancing the effectiveness of the educational process, teaching students to effectively use digital tools for educational purposes and in various areas of life. Digital literacy in the process of education implies knowledge and skills in using a wide range of digital tools, such as smartphones, tablets, computers, etc., for various educational goals. The idea of lifelong learning is one of the important directions of the educational process in Ukraine, the implementation of which is aimed at the development of society's digitalization, which requires teachers to have a high level of digital literacy. A teacher should be prepared to implement professional activities using digital technologies, utilizing the possibilities of these technologies to improve the quality of the educational process and prepare students for successful life in modern society. Digital literacy is crucial in the process of teachers' professional development, which is manifested in solving various tasks involving the use of digital technologies. Various ways of forming digital literacy can be introduced in the system of postgraduate education in Ukraine, namely: programs and courses aimed at forming digital literacy for teachers. The article presents the main directions of such programs and their content.